(untitled) (Journal of Educational Sciences, 2024)
The article presents the results of a study aimed at identifying the challenges faced by rural English as a Foreign Language (EFL) teachers in Kazakhstan when conducting research. A quantitative approach was used, using a Likert scale questionnaire completed by 81 participating teachers. The quantitative findings indicate that rural EFL teachers generally recognize the value of research in improving teaching practice and performance. However, the teachers also described significant obstacles to engaging in research, including a lack of research knowledge and skills, heavy teaching workloads that leave little time for research, and limited training and institutional support for professional development in this area. These challenges were perceived similarly across teachers with different qualification levels, suggesting systemic issues in the rural educational context. The results suggest a need to enhance research capacity among rural EFL teachers through targeted training programs, mentoring initiatives, and workload adjustments to empower them to utilize research more effectively in their teaching. The authors offered recommendations. Key words: research competence, teacher professional development, EFL teachers, research challenges, research engagement